Relationships between company size, types of production system and supply chain management: evidence from electro-electronics sector in Brazil - Jabbour, Ana Beatriz Lopes de Sousa [UNESP]; Alves Filho, Alceu Gomes; Viana, Adriana Backx Noronha; Jabbour, Charbel José Chiappetta (My University, 2011)
Purpose – The purpose of this paper is to investigate how company size and the type of production system affect the adoption of supply chain management (SCM) practices in companies in the electro‐electronics sector in Brazil. Design/methodology/approach – An e‐mail survey of 107 companies associated with the Brazilian Electrical and Electronics Industry Association (ABINEE) was conducted. Statistical techniques were employed to verify the adoption of SCM practices according to the size of the company and its production system. Findings – The major results indicate that the larger the size of the company, the higher the level of adoption of SCM practices, and that the choice of SCM practices depends upon the type of production system implemented. Practical implications – The implications of this study are useful to top management leaders of small and medium‐sized enterprises since the findings enable them to identify the most common practices adopted by either large‐, medium‐ or small‐sized companies in order to benchmark the level of adoption of SCM practices. Production managers can also benefit from this study by identifying the SCM practices that may support certain production systems.
Keywords: Brazil; Supply chain management; Electronics industry; Manufacturing systems